Nanoparticles and Their Antibacterial Application in Endodontics - Nicoletta Capuano; Alessandra Amato; Federica Dell'Annunziata; Francesco Giordano; Veronica Folliero; Federica Di Spirito; Pragati Rajendra More; Anna De Filippis; Stefano Martina; Massimo Amato; Massimiliano Galdiero; Alfredo Iandolo; et al. (MDPI AG, 2023)
Root canal treatment represents a significant challenge as current cleaning and disinfection methodologies fail to remove persistent bacterial biofilms within the intricate anatomical structures. Recently, the field of nanotechnology has emerged as a promising frontier with numerous biomedical applications. Among the most notable contributions of nanotechnology are nanoparticles, which possess antimicrobial, antifungal, and antiviral properties. Nanoparticles cause the destructuring of bacterial walls, increasing the permeability of the cell membrane, stimulating the generation of reactive oxygen species, and interrupting the replication of deoxyribonucleic acid through the controlled release of ions. Thus, they could revolutionize endodontics, obtaining superior results and guaranteeing a promising short- and long-term prognosis. Therefore, chitosan, silver, graphene, poly(lactic) co-glycolic acid, bioactive glass, mesoporous calcium silicate, hydroxyapatite, zirconia, glucose oxidase magnetic, copper, and zinc oxide nanoparticles in endodontic therapy have been investigated in the present review. The diversified antimicrobial mechanisms of action, the numerous applications, and the high degree of clinical safety could encourage the scientific community to adopt nanoparticles as potential drugs for the treatment of endodontic diseases, overcoming the limitations related to antibiotic resistance and eradication of the biofilm.